Prisoner of Zenda [videorecording (DVD)] - Cromwell, John, 1886-1979; Thorpe, Richard, 1896-1991; Colman, Ronald, 1891-1958; Carroll, Madeleine, 1906-1987; Astor, Mary, 1906-1987; Niven, David, 1910-1983; Fairbanks, Douglas, Jr., 1909-2000; Granger, Stewart, 1913-1993; Kerr, Deborah, 1921-2007; Greer, Jane, 1924-2001; Mason, James, 1909-1984; Hope, Anthony, 1863-1933 (Literary classics., 2007)
He has the appearance and manner of the king, yet he's really a lookalike ... and on his shoulders rests all hope of foiling a blackguard's plot to usurp the throne. Adventure, pageantry and royal intrigue are forged at sword point.